Between calculation and inspiration: a study of perception on the Arts in students of economics and business sciences and education - Barrantes Fernández, Telma; Cruz Hidalgo, Esteban; Bethencourt Cruz , Jonathan (Revista Complutense de Educación, 2025)
INTRODUCTION: The aim of this study is to investigate the perception of students in economics, business, and education fields regarding the arts, and whether there are differences between these groups. Drawing upon literature, students in Higher Education in economics and business fields tend to exhibit more selfish behavior and lean towards a purely monetary cost-benefit analysis. The hypothesis we work with is that they will also do so regarding artistic activities and products. METHOD: To test these hypotheses, a questionnaire was administered to students at the University of Extremadura. This involved 219 university students from education and economics backgrounds. The designed instrument allows for gathering information on various utilities, skills, and contexts to develop arts education through various descriptive, inferential analyses, and reliability indices. RESULTS: The findings suggest significant differences in their attitudes and ways of conceptualizing the use of arts. DISCUSSION: As a conclusion of the study, the importance of unlinking arts education from limiting stereotypes and promoting arts education across disciplines in higher education is emphasized.